Depression symptoms, anxiety and personality traits in patients with coronary artery disease versus patients with chronic pancreatitis hospitalised due to exacerbation of the disease - Szalewska, Dominika Anna; Szidlewska, Małgorzata; Skoczkowska-Nedoszytko, Marta; Elkady, Mohamed Amr (Family Medicine & Primary Care Review, 2016)
Background . Coronary artery disease (CAD ) is a common cause of hospitalisation in cardiac wards, while chronic pancreatitis (CP) is in gastroenterology wards. Both diseases are chronic and the clinical picture is dominated by pain. Objectives . The objective was to describe the psychological characteristics of patients hospitalised for the worsening of CAD and CP. Material and methods. The sample comprised 30 patients with CAD and 30 with CP. Participants completed personal questionnaires, the Eysenck Personality Questionnaire-Revised, STAI , Beck Depression Inventory and Scale A-Framingham. Results . Mild depression occurred in 20% of patients with CAD and 30% with CP. A severe degree of depression was found in 20% of patients with CAD and in 15% with CP while the highest levels of anxiety (9–10 sten) were found in 30% of patients with CP and in 20% of patients with CAD . In relation to introversion-extraversion personality dimension, 74% of patients with CAD and 53% of patients with CP were classified as ambivert or introvert. In both groups, most patients had moderate emotional balance as follows: 47% patients with CAD and 43% with CP. Conclusions . Compared to patients with CAD , patients with CP presented more severe depression symptoms and anxiety. The subjects with high intensification of neurotic traits more often presented high levels of anxiety and depression wherein more than half of these patients had severe anxiety and depression. Patients with low physical activity had significantly higher levels of anxiety than patients who were active daily or several times per week.